No nitrogen fractionation on 600 au scale in the Sun progenitor analogue OMC–2 FIR4. Issue 3 (20th February 2020) - Fontani, F; Quaia, G; Ceccarelli, C; Colzi, L; López-Sepulcre, A; Favre, C; Kahane, C; Caselli, P; Codella, C; Podio, L; Viti, S
ABSTRACT: We show the first interferometric maps of the 14 N/ 15 N ratio obtained with the Atacama Large Millimeter Array (ALMA) towards the Solar-like forming protocluster OMC–2 FIR4. We observed N2 H +, 15 NNH +, N 15 NH + (1–0), and N2 D + (2–1) from which we derive the isotopic ratios 14 N/ 15 N and D/H. The target, OMC–2 FIR4, is one of the closest analogues of the environment in which our Sun may have formed. The ALMA images, having synthesized beam of ∼1.5 arcsec × 1.8 arcsec, i.e. ∼600 au, show that the emission of the less abundant isotopologues is distributed in several cores of ∼10 arcsec (i.e. ∼0.02 pc or 4000 au) embedded in a more extended N2 H + emission. We have derived that the 14 N/ 15 N ratio does not vary from core to core, and our interferometric measurements are also consistent with single-dish observations. We also do not find significant differences between the 14 N/ 15 N ratios computed from the two 15 N-bearing isotopologues, 15 NNH + and N 15 NH + . The D/H ratio derived by comparing the column densities of N2 D + and N2 H + changes by an order of magnitude from core to core, decreasing from the colder to the warmer cores. Overall, our results indicate that: (1) 14 N/ 15 N does not change across the region at core scales, and (2) 14 N/ 15 N does not depend on temperature variations. Our findings also suggest that the 14 N/ 15 N variations found in pristine Solar system objects are likely not inherited from the protocluster stage, and hence the reason has to be found elsewhere.